Reliability Enhancement in Software Testing – An Agent-Based Approach for Complex Systems - Dhavachelvan, P.; Uma, G. V. (Intelligent Information Technology, 2004)
Although each paradigm have their own influence in the software engineering field with the support of their merits, researchers continue to strive for more efficient and powerful techniques. Agents are being advocated as a next generation model for engineering complex, distributed systems. Since the agent-oriented decomposition is an effective way of partitioning the problem space of complex system it has become a trend in software engineering. Although there are an increasing number of deployed agent applications, there is no systematic analysis precisely what makes the agent paradigm effective, when to use it and what type of applications can get use of it. Moreover the qualitative analysis of agent-based software engineering would not permit an objective observer to distinguish and prefer the agent-based approach from other approaches in the field of software engineering (includes software testing). Hence, the distinguishing factor cannot be just with qualitative descriptions; rather, it must be quantitative in nature. This paper therefore provides a timely summary and enhancement of agent theory in software testing, which describes an evaluation framework based on quantitative theory for adapting Agent-Oriented Software Testing (AOST) to complex systems.The multi-agent system illustrated here, is on the basis of few basic operational real-world testing techniques, as an attempt to describe how to practice agent-based software testing, which has not previously done.